Impact of metal salts on the survival, development, and oviposition behavior of coconut rhinoceros beetle (Coleoptera: Scarabaeidae) - Vowell, Tomie; Manley, Megan E.; Ho, Jordie R.; Watanabe, Shizu; Melzer, Michael J. (Frontiers in Insect Science, 2023)
Oryctes rhinoceros (Coleoptera: Scarabaeidae) life stages were acutely and chronically exposed to several metal salts at increasing concentrations to determine the impact of these salts on survival, development, and oviposition behavior. Acute (7 day) exposure to mulch rehydrated in solutions of CaCl2, KCl, MgCl2, or NaCl increasing from 0 to 0.7 M resulted in increasing mortality, with concentrations >0.5 M generally being 100% lethal to both 1st and 2nd instar larvae. A similar trend in survival was observed in subsequent experiments using a horticultural grade of Epsom salt (MgSO4) at 1X, 2X, and 5X the recommended application rate. Chronic exposure (eggs reared on mulch through pupation) to Epsom salt at these same rates resulted in significantly delayed instar development and reduced adult biometrics at both 1X and 2X levels. Similar to the acute exposure, eggs exposed to 5X levels either did not hatch or the 1st instar died soon after emergence. In choice experiments, gravid females showed no oviposition preference for media hydrated with water or 2X Epsom salt, but did avoid ovipositing in mulch rehydrated in 5X Epsom salt. These trials demonstrate a potentially novel approach to managing pest populations of O. rhinoceros.